PENGARUH SUBSTITUSI TEPUNG KEDELAI (glycine max (l.) Merill) TERHADAP MUTU ORGANOLEPTIK DAN KADAR ZAT GIZI MAKRO BROWNIES KUKUS SEBAGAI ALTERNATIF SNACK BAGI ANAK PENDERITA KEP - Harleni Harleni; Glaurensi Nidia (JURNAL KESEHATAN PERINTIS, 2017)
To overcome health problems need to be done improve peoples eating habits that is by diversification and substitution of food with food that is easily available and rich in nutrients. Soybean flour is a good food to be used as an additional ingredient in the manufacture of brownies rich in protein. The pupose of this study was to determine the effect of soybean meal substitution on organoleptic quality and macro brownies nutritional content as an alternative snack for children who KEP. This research is an experimental research using a complate randomized design consisting of four treatments and one repeatation. The analysis of variance to see the diference of treatment groups. If the result are significantly different then proceed with duncan test new multiple range test. This study was conducted from january to may 2018 and the observations made were subjectively subjected to organoleptic quality test with a panelist of approximately 25 children from the age of 3-10 years. The results showed that brownies (substitution of 10g soy flour) were the most preferrred brownies with a panelist of energy 409,42 kkal, carbohydrate 48,01%, protein 3,45%, fat 22,62%, and 25,92% moisture content. It is suggested to further researchers to observe the shelf life of the biscuits with the substitution of sweet purple potato flour and catfish flour so good for consumption by children who KEP